ANALISIS POLA ASUH OTORITATIF ORANG TUA DALAM PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA DI SEKOLAH DASAR - Celly Noer Padilah; Ihsan Rizali; Rukman Aca (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the role of parental parenting support in improving the reading comprehension skills of Phase C elementary school students. The study was motivated by the importance of reading comprehension as a fundamental skill that supports students' academic achievement. A qualitative method with a case study approach was employed. Data were collected through student observations, questionnaires distributed to parents, in-depth interviews, parenting education sessions for parents, and documentation. The observation results indicated that 5 students (30%) were categorized as having good reading comprehension skills, 3 students (5%) were in the moderate category, and 8 students (65%) were in the low category. The interview findings revealed that parental support varied, including warmth and involvement, reasoning through rules and consequences, democratic participation, and positive parent–child interactions. Students raised under an authoritative parenting style tended to demonstrate better reading comprehension skills than those whose parents adopted authoritarian or permissive parenting styles. This study concludes that both emotional and instrumental parental support contributes significantly to the improvement of students' reading comprehension skills. These findings may serve as a reference for teachers, schools, and policymakers in designing family-based literacy programs.